Chinese life purpose orientation questionnaire: assessing purpose orientations among Chinese college students. Issue 2 (3rd April 2022) - Wang, Tong; You, Xu Qun; Huang, Xi Ting
Abstract: Life-purpose orientations can highly influence people's life paths and well-being. However, existing psychological measurements tend to dismiss the need for assessing the individual's life purpose orientations, especially in non-Western cultures. This study sought to develop a new measure to assess purpose orientations specific to the Chinese context. We first built the item pool of Chinese college students' life purpose orientations (Study 1). This was followed by conducting an initial testing of the item pool, and developing a preliminary six-dimension Chinese Life Purpose Orientation Questionnaire (Study 2). Further revision supported a five-dimension questionnaire with adequate validity and reliability (Study 3). The measure's validity and reliability were discussed, and the limitations also were addressed.